Digital-Based Listening Materials in the Merdeka Curriculum: A Narrative Review - Teti Elawati; Nazwa Khalifatunnisa (PT. Intelek Cendikiawan Nusantara, 2025)
This narrative review examines the use of digital listening materials in the Merdeka Curriculum in Indonesia. The Merdeka Curriculum is implemented to fulfill 21st-century learning guidelines in terms of material effectiveness, flexibility, and graduate profile confirmation. Listening skills are fundamental in English language learning, but remain a challenge for students of English as a foreign language (EFL) due to the lack of explanation of the original context. This review uses a narrative review method, examining articles or journals published between 2021 and 2025 that discuss digital media in learning and teaching listening skills. The findings report that podcasts, audio-video, YouTube platforms, AR/VR applications, and digital worksheets related to audio are widely used to develop in-depth listening comprehension. These materials provide credible input, flexible access, multimodal experiences, and support a student-centered approach in the Merdeka Curriculum. However, several challenges remain, including teacher readiness in utilizing teaching materials through digital tools, a lack of local cultural content, and insufficient links to formative assessment. In general, digital-based listening resources are effective in developing context-appropriate meaning-making and deep thinking, in line with the curriculum's emphasis on creativity, independence, and 21st-century competencies. Future research should focus on teacher training, cultural adaptation, and assessment integration to maximize the potential of listening materials.